PENGARUH FINANCIAL DISTRESS, CAPITAL INTENSITY, UKURAN PERUSAHAAN DAN RISIKO PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Annisa Mayang Arista Sembiring Arista Sembiring; Irwan Setiawan (JURNAL KONSISTEN, 2024)
Purpose. This study aims to determine the effect of financial distress, capital intensity, firm size and risk corporate on tax avoidance. Methods. This research is a quantitative research type. The population in this study are banking sector companies listed on the Indonesia Stock Exchange in 2018 – 2022. The data used in this study are secondary data in the form of annual reports. The sampling technique used is purposive sampling, where from 47 companies in the banking sector, a sample of 10 companies is obtained for 5 consecutive years of observation so that the total sample obtained was 50. The analysis used is a panel data regression analyst using a common effect regression model. Results. The results obtained partially show that the financial distress has effect on tax avoidance, capital intensity has effect on tax avoidance, firm size has no effect on tax avoidance, and risk corporate has no effect on tax avoidance. Implications. That simultaneously financial distress, capital intensity, firm size and risk corporate has effect on tax avoidance. Keywords